Translating biomarker insights into practice: a path forward in TA-TMA management - Sonata Jodele; Eleni Gavriilaki (Frontiers in Medicine)
Recent advances in the management of transplant-associated thrombotic microangiopathy (TA-TMA) include the harmonization of diagnostic criteria and the identification of high-risk disease features. Individual hematologic and complement biomarkers show moderate specificity when used alone in the detection of TA-TMA in hematopoietic stem cell transplant (HSCT) recipients, but the identification of endothelial injury due to microangiopathic process can be enhanced using longitudinal monitoring of biomarkers and clinical features. An increase in the sC5b-9 level reflects terminal complement activation, a hallmark of TA-TMA pathogenesis that guides therapeutic interventions. In addition, distinguishing physiologic from pathologic complement activation is essential for timely diagnosis of the disease and selection of targeted interventions. Eculizumab therapy, a biomarker-guided C5 blocker, significantly improves clinical outcomes in severe TA-TMA; however, there is a lack of knowledge on how to select second-line complement inhibitors or combination therapies for cases with a suboptimal response to eculizumab. This article proposes practical approaches to increasing the specificity and attributability of TA-TMA diagnostic biomarkers by integrating clinically available supportive diagnostic tests and provides insights into potential biomarkers for currently available novel complement inhibitors. These findings help ensure timely diagnosis, prevent irreversible organ injury, and improve outcomes in HSCT recipients with TA-TMA.